1998
DOI: 10.1200/jco.1998.16.6.2142
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node staging in non-small-cell lung cancer with FDG-PET scan: a prospective study on 690 lymph node stations from 68 patients.

Abstract: PET + CT is significantly more accurate than CT alone in LN staging of NSCLC. A five-point visual scale is as accurate as the use of an SUV threshold for LNs in the distinction between benign and malignant nodes. The very high negative predictive value of mediastinal PET could reduce the need for mediastinal ISS in NSCLC substantially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
145
0
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(155 citation statements)
references
References 25 publications
3
145
0
7
Order By: Relevance
“…Furthermore, maximum SUV was as accurate as mean SUV in lymph node staging of lung cancer [25]. Optimal cutoff values of maximum SUV for lymph node metastasis in the present study were 4.4 for N1-N3 and 4.8 for N1-N2 lymph nodes, values that are similar to those of recently published results (SUVmax = 4.4-4.5) [26,27]. These values were not significantly changed in the ILD 1-3 and ILD 1-2 groups , and their sensitivity and specificity were moderate (sensitivity = 68.8%, specificity = 74.6-75.8%).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, maximum SUV was as accurate as mean SUV in lymph node staging of lung cancer [25]. Optimal cutoff values of maximum SUV for lymph node metastasis in the present study were 4.4 for N1-N3 and 4.8 for N1-N2 lymph nodes, values that are similar to those of recently published results (SUVmax = 4.4-4.5) [26,27]. These values were not significantly changed in the ILD 1-3 and ILD 1-2 groups , and their sensitivity and specificity were moderate (sensitivity = 68.8%, specificity = 74.6-75.8%).…”
Section: Discussionsupporting
confidence: 90%
“…It is quite possible that patients with inflammatory lung disease had more false-positive lymph nodes with low to intermediate 18 F-FDG uptake and, thus, a higher-than-usual SUV was obtained for the highest accuracy. A visual interpretation is widely used for clinical PET interpretation of lymph node involvement [25][26][27][28][29][30][31]. Most of the previous comparative studies demonstrated that visual analysis of PET is superior or comparable to the semiquantitative method except for N3 lymph nodes [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high NPV of 18 F-FDG PET/CT (up to 97%) for mediastinal disease6971 has led to the recommendation to omit mediastinoscopy in patients with negative mediastinal 18 F-FDG PET/CT 707273. However, special attention should be paid to central tumors, which have a high incidence of occult N2 disease 74.…”
Section: Methodsmentioning
confidence: 99%
“…FDG accumulation within the primary lung cancer on the attenuation-and decay-corrected images was graded independently. A 5-point visual grading system (a modified method of Vansteenkiste et al (Vansteenkiste et al 1998)) was used to interpret FDG uptake within the primary lesions without the pathological information; including no increased uptake (similar to background), weak uptake (lower than mediastinum), medium uptake (similar to mediastinum), strong uptake (higher than mediastinum), and very strong uptake (remarkably higher than mediastinum).…”
Section: Patients and Mthodsmentioning
confidence: 99%